Novel Implications of MicroRNAs, Long Non-coding RNAs and Circular RNAs in Drug Resistance of Esophageal Cancer - Wei, Ling; Sun, Jujie; Zhang, Nasha; Shen, Yue; Wang, Teng; Li, Zengjun; Yang, Ming (Frontiers in Cell and Developmental Biology, 2021)
Esophageal cancer is the eighth most common malignancy and the sixth leading cause of cancer-related deaths worldwide. Chemotherapy based on platinum drugs, 5-fluorouracil, adriamycin, paclitaxel, gemcitabine and vinorelbine, as well as targeted treatment and immunotherapy with immune checkpoint inhibitors improved the prognosis in a portion of patients with advanced esophageal cancer. Unfortunately, a number of esophageal cancer patients develop drug resistance, resulting in poor outcomes. Multiple mechanisms contributing to drug resistance of esophageal cancer have been reported. Notably, noncoding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), have been identified to play crucial roles in modulating esophageal cancer drug resistance. In the present review, we highlight the underlying mechanisms how miRNAs, lncRNAs and circRNAs impact the drug resistance of esophageal cancer. Several miRNAs, lncRNAs and circRNAs may have potential clinical implications as novel biomarkers and therapeutic targets for esophageal cancer.